1983
DOI: 10.1136/bmj.286.6375.1405
|View full text |Cite
|
Sign up to set email alerts
|

Five hundred patients with myocardial infarction monitored within one hour of symptoms.

Abstract: Of 2886 patients monitored during acute myocardial infarction, 500 were observed within one hour of the onset of symptoms. Half of the early admission group were admitted in response to emergency 999 calls and 435 of them travelled in resuscitation ambulances, where surveillance for arrhythmias was instituted. Pulmonary oedema occurred in 130 patients (26%), cardiogenic shock supervened in 60 (12%), and 115 (23%) died in hospital. Ventricular fibrillation was observed in 98 patients (20%). Forty two of them su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
5

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(37 citation statements)
references
References 15 publications
0
32
0
5
Order By: Relevance
“…In previous studies (albeit without the use of Holter recording), it was reported to occur in 2.3% to 5.3% of patients during the first day"',24 and in 2.5% to 15% of patients during the first 2 weeks.22'25-28 The incidence is always lower in thrombolysed patients (eg, in the ISAM study, 4.3% versus 5.3% on day 124; in the ISIS-2 study, 4.4% versus 5.0% within 10 days25), but the very low incidence in our series may also be related to (1) the low-risk profile of our patients as discussed above and (2) a delayed start of the recording, missing the first 2.5 hours of chest pain. 3 The incidence of nonsustained VT (75%) or of AIVR (71%) in our series is much higher than the previously reported data of trials without Holter recording24 or with recording during a limited time period,29 since the benign hemodynamic effect of these arrhythmias may calculated figures in some smaller studies using Holter: 70% to 90% for nonsustained VT22,27,30 and 77% to 90% for AIVR.2227303' A noteworthy observation is that none of the patients with major arrhythmias during the first day had malignant recurrences during the ensuing 2 weeks (and vice versa). The limited size of our study and the low incidence of major events in our low-risk patients, Summarizing, we may conclude that (1) our data do not support the hypothesis that ,-blockers or bradycardiac agents might reduce the incidence of arrhythmias when used in conjunction with thrombolytic therapy, with the possible exception of atrial fibrillation in the alinidine group; (2) the pathogeneses of VT and VF early during acute myocardial infarction are clearly distinct; (3) VT or VF during the first 2 weeks is a marker for a larger infarct; (4) we could not detect a relation between malignant arrhythmias on day 1 and recurrences within the following 2 weeks; and (5) the presence of ST-segment normalization combined with the occurrence of a long run of AIVR predicts coronary reperfusion.…”
Section: Sustained Ventricular Tachycardia and Ventricular Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies (albeit without the use of Holter recording), it was reported to occur in 2.3% to 5.3% of patients during the first day"',24 and in 2.5% to 15% of patients during the first 2 weeks.22'25-28 The incidence is always lower in thrombolysed patients (eg, in the ISAM study, 4.3% versus 5.3% on day 124; in the ISIS-2 study, 4.4% versus 5.0% within 10 days25), but the very low incidence in our series may also be related to (1) the low-risk profile of our patients as discussed above and (2) a delayed start of the recording, missing the first 2.5 hours of chest pain. 3 The incidence of nonsustained VT (75%) or of AIVR (71%) in our series is much higher than the previously reported data of trials without Holter recording24 or with recording during a limited time period,29 since the benign hemodynamic effect of these arrhythmias may calculated figures in some smaller studies using Holter: 70% to 90% for nonsustained VT22,27,30 and 77% to 90% for AIVR.2227303' A noteworthy observation is that none of the patients with major arrhythmias during the first day had malignant recurrences during the ensuing 2 weeks (and vice versa). The limited size of our study and the low incidence of major events in our low-risk patients, Summarizing, we may conclude that (1) our data do not support the hypothesis that ,-blockers or bradycardiac agents might reduce the incidence of arrhythmias when used in conjunction with thrombolytic therapy, with the possible exception of atrial fibrillation in the alinidine group; (2) the pathogeneses of VT and VF early during acute myocardial infarction are clearly distinct; (3) VT or VF during the first 2 weeks is a marker for a larger infarct; (4) we could not detect a relation between malignant arrhythmias on day 1 and recurrences within the following 2 weeks; and (5) the presence of ST-segment normalization combined with the occurrence of a long run of AIVR predicts coronary reperfusion.…”
Section: Sustained Ventricular Tachycardia and Ventricular Fibrillationmentioning
confidence: 99%
“…(2) The pathogeneses of VT and VF early during AMI are clearly distinct. (3) VT or VF during the first 2 weeks is a marker for a larger infarct. (4) We could not detect a relation between malignant arrhythmias on day 1 and recurrences within the following 2 …”
mentioning
confidence: 99%
“…O maior risco de fibrilação ventricular ocorre durante as primeiras 4h após o início dos sintomas 599,609 . A fibrilação ventricular observada na fase aguda (geralmente nas primeiras horas) do infarto, chamada de "fibrilação ventricular primária", ocorre em 4% a 18% dos pacientes com infarto [610][611][612] .…”
Section: -Parada Cardiorrespiratóriaunclassified
“…Reports have described the shortening of decision time by means of early recognition of symptoms by education of patients, 5 the 'chain of survival' concept advocated by the American Heart Association, 6 thrombolytic therapy, 7-13 anticoagulant therapy, 7,8,14,15 emergency PTCA, 13,[16][17][18][19][20][21][22][23] assisted circulation 24,25 and a system to determine the effect of prehospital-initiated treatment of myocardial infarction. 26,27 Many reports have shown that case-fatality rates of AMI patients arriving quickly at specialty institutions are decreased by recanalization therapy and assisted circulation in contrast to patients not so treated.…”
Section: Discussionmentioning
confidence: 99%